DESAIN MOCKUP APLIKASI PARKIR.ID MENGGUNAKAN DESIGN THINKING - Maulidia Nur Anggraini; Tiawan; Zia Imam Perdana; Lila Setiyani; Ahmad Najib Mutawally; Annizar Mohammad Fardani; Anggun Marfela; Alben Mardiansyah; Intan Wulandari (Program Studi Informatika Universitas Teknologi Sumbawa, 2024)
Parkir.Id application design research addresses the issue of illegal parking in urban areas, aiming to alleviate difficulties such as finding safe parking, lack of information, and poor communication with parking service providers. Employing Design Thinking, the study develops an intuitive and responsive application mockup through five stages: empathy, definition, ideation, prototyping, and testing. Through interviews and surveys, user needs and issues are understood, leading to the identification of primary problems. Various design concepts are then generated and refined based on user feedback. The resulting Parkir.Id mockup facilitates users in locating safe parking, offering prompt information, and fostering efficient communication with service providers. Demonstrating the effectiveness of Design Thinking, this study provides user-centered solutions to illegal parking, enhancing user efficiency and comfort in managing parking.